Actin Is a Target of T-Cell Reactivity in Patients with Advanced Carotid Atherosclerotic Plaques - Profumo, Elisabetta; Buttari, Brigitta; Petrone, Linda; Lacroce, Giada; Tesori, Maria Chiara; Capoano, Raffaele; Salvati, Bruno; Riganò, Rachele (Mediators of Inflammation, 2013)
Atherosclerosis is a chronic inflammatory disease of the arterial wall associated with autoimmune reactions. In a previous study, we observed the presence of actin-specific antibodies in sera from patients with carotid atherosclerosis. To extend our previous results we evaluated the possible role of actin as antigenic target of cell-mediated immune reactions in carotid atherosclerosis. Peripheral blood mononuclear cells (PBMC) from 17 patients and 16 healthy subjects were tested by cell proliferation assay and by ELISA for cytokine production. Actin induced a proliferative response in 47% of patients’ PBMC samples, with SI ranging from 2.6 to 21.1, and in none of the healthy subjects’ samples (patients versus healthy subjects, P=0.02). The presence of diabetes in patients was significantly associated with proliferative response to actin (P=0.04). IFN-γ and TNF-α concentrations were higher in PBMC from patients than in those from healthy subjects and in PBMC proliferating to actin than in nonproliferating ones. Our data demonstrate for the first time a role of actin as a target autoantigen of cellular immune reactions in patients with carotid atherosclerosis. The preferential proinflammatory Th1 activation suggests that actin could contribute to endothelial dysfunction, tissue damage, and systemic inflammation in carotid atherosclerosis.